Penerapan Problem Based Learning Berbantuan Lembar Kerja Siswa Untuk Meningkatkan Hasil Belajar Pada Mata Pelajaran Pemrograman Dasar (Studi Pada : SMK Negeri 4 Malang) - Sila Nur Ma'rifah; Satrio Hadi Wijoyo; Satrio Agung Wicaksono (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2019)
This research is motivated by the learning process that takes place centered on the teacher's explanation, there is no student companion in learning and student learning outcomes from assignments are not good enough. This study aims to improve student learning outcomes in Basic Programming subjects by using Problem Based Learning aided by Student Worksheets. This study uses a Quasi Experiment method with a Non Equivalent Control Group Design that uses two classes as a control and an experiment. This study uses the subject of class X students of the Department of Multimedia SMK 4 Malang. Class X MM A is the superior class and X MM B is the lowest class. This study uses data collection techniques with test instruments in the form of Pre-Test and Post-Test questions in the form of 5 descriptive questions. This study uses data processing techniques with the Wilcoxon Test and the Mann-Whitney Test. This study results in an increase in learning outcomes with learning that applies Problem Based Learning with or not with the help of Student Worksheets because it gets a smaller number than the significant level used by 0.05, and learning outcomes on students' knowledge and skills are both the same at students with learning who apply Problem Based Learning with or not with the help of Student Worksheets because they get a number greater than the significant level used by 0.05.